Critical Review: Emotion: A Religio-Psychological Explanation Of Human Emotions In The Qur’an From Darwis Hude - Amiruddin Nahrawi (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2020)
The dissertation written by M. Darwis Hude entitled